Effect of Sb and N resonant states on the band structure and carrier effective masses of GaAs1-x-yNxSby alloys and GaAs1-x-yNxSby/GaAs quantum wells calculated using k·p Hamiltonian. (June 2017) - Mal, Indranil; Samajdar, D.P.; Das, T.D.
Abstract: GaAsNSb is a promising candidate for use in GaAs-based optoelectronic devices in the 1.33–1.55 μm wavelength region. We have calculated the band structure of dilute nitride-antimonide GaAs1–x–y Nx Sby alloys, lattice matched to GaAs, using Band anticrossing (BAC) and Valence Band Anticrossing (VBAC) model in conjugation withk·p Hamiltonian method. This mathematical model in the form of a 16 band Hamiltonian matrix is used to examine the shift of different bands as a function of Sb concentration for both bulk and quantum well structures for GaAsNSb/GaAs. The band parameters such as energy gap, spin-orbit splitting energy, carrier effective masses, band offsets, and strain generated due to the growth of GaAsNSb/GaAs heterostructures as a function of Sb and N concentrations are calculated and compared with the recent experimental data. The substitution of As atoms due to the incorporation of N and Sb impurity atoms causes a significant band gap reduction of ∼330 meV for GaAs0.931 Sb0.05 N0.019 alloys. The enhancement of spin-orbit splitting energy causes a crossover between Eg and Δ s o for Sb and N concentration of 27 and 10 at % respectively. Suitable tuning of the band offset values with Sb and N concentrations makes GaAsNSb/GaAs alloy system an efficient alternative for band gap engineering and fabricating photonic device structures. Highlights: Band structure of GaAsNSb alloys and GaAsNSb/GaAs QWs calculated using 16 band k dot p Hamiltonian. Carrier effective masses, band offsets and strain calculated as function of Sb and N concentration. Band gap of GaSbBiN calculated using k dot p method, VBAC and CBAC models. Larger values of calculated Conduction band offset can help in carrier confinement. Quantum confinement potential and energy levels calculated for 10 nm wide GaAsNSb/GaAs QWs.